Intervention intended to improve public health professionals' self-efficacy in their efforts to detect and manage perinatal depressive symptoms among Thai women: a mixed-methods study - Nitikorn Phoosuwan; Pranee C. Lundberg; Sadiporn Phuthomdee; Leif Eriksson (BMC, 2020)
Abstract Background Targeting perinatal depressive symptoms among women can reduce premature mortality. However, public health professionals (PHPs) in primary healthcare settings often have low self-efficacy for detection and management of perinatal depressive symptoms among women. This mixed-methods study was aimed at developing and evaluating a self-efficacy improvement programme (SIP) intended to increase PHPs' self-efficacy in efforts to detect and manage perinatal depressive symptoms. Methods The SIP consisted of 1 day of theory and 4 weeks of practice. Sixty-six PHPs from sub-district health promotion hospitals (primary health care level) in Sakonnakhon, a north-eastern province in Thailand, were randomised into an intervention group (n = 33) and a control group (n = 33). Twenty-three of the intervention group participants also took part in focus group discussions (FGDs). Multiple linear regression and qualitative content analysis were used to analyse the data. Results After the SIP, the intervention group participants had higher self-efficacy score than those in the control group (p = 0.004). The FGDs resulted in four categories emerging: Having confidence, Changing knowledge and attitudes, Increasing perception of an important role, and Increasing awareness of performed function. Conclusions To enhance the ability of PHPs to detect and manage perinatal depressive symptoms, an intervention programme based on self-efficacy modification is recommended.